IDDF2022-ABS-0006 Efficacy of ustekinumab on perianal fistulizing CD: a retrospective single-center real-world analysis. (2nd September 2022) - Yao, Jiayin; Peng, Xiang; Zhao, Junzhang; Zhi, Min
Abstract : Background: Perianal fistula is the most common complication of Crohn's disease (CD), affecting approximately 40% of patients. It represents an aggressive phenotype of CD, which may respond poorly to medications, has a high risk of relapse and disease-associated disability, and face early-onset surgery. Data on Ustekinumab (UST) in treating perianal fistulizing CD are limited in China. We aimed to evaluate the efficacy of UST in a real-world setting. Methods: We retrospectively analyzed patients with perianal fistulizing CD and receiving UST treatment from March 1, 2020 to October 30, 2021. Patients' characteristics, biomarkers, and imaging were extracted from digital databases. Results: Twenty patients were eligible (18 males; mean age of 29.4±2.6 years; mean disease duration of 6.3±0.9 years; 45.0% diagnosed as complex fistula; mean baseline Van Assche score of 7.7±1.1). Perianal Crohn's disease activity index (5.4±1.0 vs 8.7±1.0, P=0.027) and Crohn's anal fistula quality of life (29.4±4.8 vs 38.9±4.2, P=0.011) reduced significantly. Clinical remission appeared in 60.0% and clinical response in 85.0%; clinical fistula remission in 30.0%, clinical fistula response in 35.0%, and no response in 35.0% of patients (IDDF2022-ABS-0006 Figure 1. Radiological evaluation of perianal fistulas. (Panel A: Radiological outcomes of perianal fistulas at week 16/20; Panel B: Van Assche scores based on MRI at baseline and week 16/20. N=8)). Eight patients received post-treatment MRI. Healing, partial response, no change, and deterioration appeared in 37.5%, 25.0%, 12.5% and 25.0% of the patients, respectively (IDDF2022-ABS-0006 Figure 1. Radiological evaluation of perianal fistulas. (Panel A: Radiological outcomes of perianal fistulas at week 16/20; Panel B: Van Assche scores based on MRI at baseline and week 16/20. N=8)). The cut-off UST trough concentration predicting clinical fistula remission was 2.6 μg/ml (an area under the curve of 0.821, sensitivity 66.7%, specificity 85.7%) (IDDF2022-ABS-0006 Figure 2. ROC curve of UST trough concentration at week 16/20 predicting clinical fistula remission). Conclusions: UST is efficacious in promoting clinical and radiological perianal fistula remission in patients with CD. A trough concentration of UST higher than 2.6μg/ml is associated with clinical fistula remission at week 16/20.